If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5m + -3 = 2m + -9 Reorder the terms: -3 + 5m = 2m + -9 Reorder the terms: -3 + 5m = -9 + 2m Solving -3 + 5m = -9 + 2m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-2m' to each side of the equation. -3 + 5m + -2m = -9 + 2m + -2m Combine like terms: 5m + -2m = 3m -3 + 3m = -9 + 2m + -2m Combine like terms: 2m + -2m = 0 -3 + 3m = -9 + 0 -3 + 3m = -9 Add '3' to each side of the equation. -3 + 3 + 3m = -9 + 3 Combine like terms: -3 + 3 = 0 0 + 3m = -9 + 3 3m = -9 + 3 Combine like terms: -9 + 3 = -6 3m = -6 Divide each side by '3'. m = -2 Simplifying m = -2
| -4(4+r)=12+3r | | x^2-5x+55=8605 | | 7x^2+14x+21=1 | | 6a-14=9a-5 | | 7t-15=4t-6 | | 1.25x=35.00+.75x | | r^3+6r^2-4r-24=0 | | x^2-5x-66= | | 0.2x=0.5+3 | | b^2-6b-16=0 | | -4+4k=2(3k+1) | | -5(2b+1)+(11b-3)=0 | | -0.05x-0.04=-0.01x | | 90-4y=50-2x | | -4+4k=(3k+1) | | 4(x+3)=52 | | x^2+18-16=0 | | 2x-8=12+x | | z^3-64z=0 | | .43w-11=-.57w | | 7x+2=3x+94 | | 9t^2+24tr+16r^2=0 | | 5[6-5x]=15x-35 | | 9(t-4)+5t=7(2t+5)-11 | | 8y=-4x-12 | | -28+15-22z=3 | | 3y+x=-1 | | 5(x-3)+12=-2(x-2) | | 28b^2-13b-6=0 | | t-36=-15 | | -r-10r(4p+2p)=0 | | 5x+7=4(x+13) |